(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The rapid integration of the Internet of Things (IoT) into healthcare, often referred to as Healthcare IoT, has ushered in a new era of personalized patient monitoring and medical care. Central to this healthcare revolution is the application of Wireless Body Sensor Networks (WSNs), which allow continuous, real-time monitoring of vital signs. However, the effectiveness of Healthcare IoT crucially depends on the development and implementation of an optimal routing protocol for WSNs. This article explores the significance of an optimal routing protocol in enhancing Healthcare IoT. It emphasizes the need for seamless, reliable, and energy-efficient data transmission, especially for real-time patient monitoring. We delve into the challenges faced in developing such routing protocols, including network congestion, security, and scalability. Innovative solutions, such as adaptive routing algorithms, enhanced security measures, and Quality of Service (QoS) awareness, are discussed. The future outlook presents a promising landscape, with advancements in routing protocols enabling the integration of artificial intelligence and machine learning in healthcare decision-making. The synergy between Healthcare IoT and an optimal routing protocol for Wireless Body Sensor Networks holds the potential to transform patient care, diagnosis, and treatment, offering a brighter, data-driven future for healthcare.